Reviewing John Locke’s Concept of Power From the Perspective of Al-Maududi - Latief, Mohamad; Pramono, Muhamad Fajar; Sansayto, Ide Mafaza (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2023)
The concept of power today is much influenced by the thoughts of John Locke. The power shaped by John Locke gives this country a liberal character. Individual rights are at the centre of all interests. In the history of Islam, some concepts have been very important in shaping Islamic perceptions of democracy. This research is library research because it is library research. The approach used is a historical-philosophical approach. This paper dissects John Locke's democratic thinking, which is analysed using the democratic thinking of a contemporary Muslim intellectual, namely Abu A'la Maududi. Theo-democracy is a system of government initiated by Al-Maududi by combining the concepts of monotheism and trias politica. The Al-Maududi Islamic State must be built on the basis of Islam, which is the main foundation of Tawhid. According to Maududi, power in the form of sovereignty is based primarily on God's sovereignty rather than the sovereignty of the people. The theo-democratic system is divided into three institutions: the legislature, executive, and judiciary.